SOLUSI POSITIF MODEL SIR - Awawin Mustana Rohmah (Unisda Journal of Mathematics and Computer Science (UJMC), 2017)
Model that describes the epidemic spread of disease can spread in this area, one of which can be formed in the mathematical model of endemic SIR (susceptible, infected, and recovery). Based on the model, we can analysis existence and uniqueness, it shows that the system has solution and unique. Furthermore SIR indicated that the model has a positive solution. The final results obtained from this study is SIR model of having a uniqueand solution, as well as solutions that model is positive.